FRI0496 Comparing tofacitinib safety profile in patients with psoriatic arthritis in clinical studies with real-world data. (15th June 2017) - Curtis, JR; Yun, H; FitzGerald, O; Winthrop, K; Azevedo, VF; Burmester, G; Rigby, WFC; Kanik, KS; Rojo, R; Menon, S; Wang, C; Biswas, P; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor under investigation for the treatment of psoriatic arthritis (PsA). Two Phase 3 studies have been completed (NCT01877668 ; NCT01882439 ) and a long-term extension (LTE) study is ongoing (database not locked; NCT01976364 ). Objectives: To compare incidence rates (IR) for adverse events (AEs) of special interest in a tofacitinib cohort from the Phase 3 PsA trials with real-world experience in a comparison cohort from the US Truven MarketScan database. Methods: The tofacitinib cohort included adult patients (pts) from 2 Phase 3 studies with ≥6 months PsA diagnosis who met ClASsification of Psoriatic ARthritis (CASPAR) criteria, had active plaque psoriasis, and active arthritis (≥3 swollen and ≥3 tender/painful joints) and who were treated with tofacitinib. Pts were grouped by those who received tofacitinib 5 (N=238) or 10 mg (N=236) twice daily (BID) in the 2 Phase 3 studies, and all pts who received ≥1 dose of tofacitinib in the 2 Phase 3 studies or the LTE (tofacitinib all doses, N=783). The comparison cohort (N=5799) comprised pts with moderate to severe PsA, defined by ≥1 inpatient or ≥2 outpatient 696.0 diagnosis codes on 2 unique calendar days (≥1 by a rheumatologist) between Oct 2010 and Sep 2015, initiating therapy with a systemic agent for PsA. Key Phase 3 study exclusion criteria were applied to the comparison cohort. IRs for serious infection events (SIEs), herpes zoster (HZ), malignancies (excluding non-melanoma skin cancer [NMSC]), NMSC and major adverse cardiovascular events (MACE) were compared. Results: Mean age, gender and diabetes history were generally similar between the tofacitinib and comparison cohorts (48.7–49.5 years, 42.4–49.2% male, 12.2–15.7% with diabetes history). Overall more pts treated with tofacitinib had prior experience with corticosteroids (15.7–28.2%), conventional synthetic disease-modifying antirheumatic drugs (100%) and tumour necrosis factor inhibitors (48.1–55.9%) vs the comparison cohort (11.9%, 46.6% and 36.6%, respectively). IRs for SIEs were lower for the tofacitinib vs the comparison cohort (Table 1 ). The tofacitinib cohort had a higher rate of HZ vs the comparison cohort (Table 1 ). IRs for malignancies and MACE were similar between cohorts (Table 1 ). Conclusions: IRs of AEs of special interest reported in tofacitinib PsA Phase 3 studies were generally comparable to those in a general PsA population comprising pts receiving a range of biologic agents, except HZ, which was higher for pts treated with tofacitinb but similar to the incidence observed with tofacitinib treatment in other indications. Acknowledgements: This study was sponsored by Pfizer Inc. Editorial support was provided by A Pedder of CMC and was funded by Pfizer Inc. Disclosure of Interest: J. Curtis Grant/research support from: Amgen, Bristol-Myers Squibb, Eli Lilly, Janssen, Pfizer Inc, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Eli Lilly, Janssen, Pfizer Inc, H. Yun Grant/research support from: Pfizer Inc, O. FitzGerald Grant/research support from: AbbVie, Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Eli Lilly, Janssen, Pfizer Inc, Speakers bureau: Celgene, Janssen, Novartis, K. Winthrop Grant/research support from: Bristol-Myers Squibb, Pfizer Inc, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Eli Lilly, Galapagos, Pfizer Inc, UCB, V. Azevedo Grant/research support from: Bristol-Myers Squibb, GSK, Pfizer Inc, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Merck Serono, Novartis, Pfizer Inc, G. Burmester Grant/research support from: UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Hexal, Janssen, MSD, Medimmune, Novartis, Pfizer Inc, Sanofi, Roche, Speakers bureau: AbbVie, Bristol-Myers Squibb, Hexal, MSD, Novartis, Pfizer Inc, Roche, W. F. Rigby Grant/research support from: Amgen, Pfizer Inc, Roche, Consultant for: Bristol-Myers Squibb, Eli Lilly, Pfizer Inc, Roche, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Rojo Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Menon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, P. Biswas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, N. Palmetto Shareholder of: Pfizer Inc, Employee of: Pfizer Inc